Faktor-faktor penyebab pelemahan kurs rupiah terhadap dollar amerika - A. Sakir A. Sakir; Zaida Rizqi Zainul; Zulkifi Zulkifi (KINERJA, 2020)
This study is observational literature to determine the factors that influence the amount of  distress value that tends to run continuously against the US dollar as the currency of  international standards. Indonesian monetary authorities policy which has floated its currency in the market has added a new problem that is now dominant external factors than internal factors  which affect the rise and fall of a country's currency exchange rate. Evidence shows that  external factors is more dominant in influencing the dollar against the rupiah pressure  indicating that the government's attention to this would have to be more focused economic  external factors than internal factors of the economy.